Bacillus amyloliquefaciens, Bacillus velezensis, and Bacillus siamensis Form an “Operational Group B. amyloliquefaciens” within the B. subtilis Species Complex - Fan, Ben; Blom, Jochen; Klenk, Hans-Peter; Borriss, Rainer (Frontiers in Microbiology, 2017)
The plant growth promoting model bacterium FZB42T was proposed as the type strain of B. amyloliquefaciens subsp. plantarum (Borriss et al., Int J Syst Evol Microbiol. 2011, vol. 61, 1786-801), but has been recently recognized as being synonymous to Bacillus velezensis due to phylogenomic analysis (Dunlap et al. Int J Syst Evol Microbiol. 2016, vol. 66, 1212-1217). However, until now, majority of publications consider plant-associated close relatives of FZB42 still as ´B. amyloliquefaciens´. Here, we reinvestigated the taxonomic status of FZB42 and related strains in its context to the free-living soil bacterium DSM7T, the type strain of B. amyloliquefaciens. We identified 66 bacterial genomes from the NCBI data bank with high similarity to DSM7T. Dendrograms based on complete rpoB nucleotide sequences and on core genome sequences, respectively, clustered into a clade consisting of three tightly linked branches: (1) B. amyloliquefaciens, (2) B. siamensis, and (3) a conspecific group containing the type strains of B. velezensis, B. methylotrophicus, and B. amyloliquefaciens subsp. plantarum. The three monophyletic clades shared a common mutation rate of 0.01 substitutions per nucleotide position, but were distantly related to B. subtilis (0.1 substitutions per nucleotide position). The tight relatedness of the three clusters was corroborated by TETRA, dDDH, ANI and AAI analysis of the core genomes, but dDDH and ANI values were found slightly below species level thresholds when B.amyloliquefaciens DSM7T genome sequence was used as query sequence. Due to these results, we propose that the B. amyloliquefaciens clade should be considered as a taxonomic unit above of species level, designated here as ´operational group B. amyloliquefaciens´ consisting of the soil borne B. amyloliquefaciens, and plant associated B. siamensis and B. velezensis, whose members are closely related and allow identifying changes on the genomic level due to developing the plant-associated life-style.